Pengaruh Kompensasi dan Kepuasan Kerja Terhadap Kinerja Karyawan di Rumah Sakit Umum Jampangkulon - Moch Alfiansyah (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2021)
The purpose of this study was to determine and analyze the influence between. The method used is causal association with a quantitative approach. Variables are measured by a Likert scale. Data processing using SPSS software version 24.0. The test method was carried out in the form of a questionnaire list of questions. In this study, the total population was narrowed from the total number of employees as many as 813 employees, by calculating the sample size using the Slovin technique so that the population became 89 people. The data analysis technique used is the classical assumption test, multiple linear regression test and the coefficient of determination test. The results showed a positive and significant influence between compensation and employee performance, job satisfaction had an effect but not significant on employee performance, and the test results jointly compensation and job satisfaction had a positive and significant effect on employee performance.